Interaksi Sosial antara Lansia dengan Pendamping di Yayasan Pondok Lansia Tulus Kasih - Haikal Ismail; Mirna Nur Alia Abdullah; Warlim Warlim (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
To help the elderly in their daily activities, good communication is needed between the elderly and the caregivers. However, the communication limitations of the elderly make interactions with caregivers run dynamically. The purpose of this research is to find out how social interactions are established between the elderly and the caregivers. This type of research is descriptive qualitative with a case study method. As for the results of this study, there are forms of associative social interactions such as accommodation and cooperation between the elderly and caregivers. Then, there are forms of dissociative social interaction, namely conflict and contravention caused by misunderstanding of communication between the elderly and the caregivers.